2018
DOI: 10.1002/jbt.22211
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine attenuates lipopolysaccharide induced acute lung injury by targeting NLRP3 via miR‐381

Abstract: Dexmedetomidine (Dex) is an agonist of α2-adrenergic receptors, and it is used as an anxiety reducing, sedative, and pain medication in clinical. Studies have shown that dexmedetomidine protects against lipopolysaccharide (LPS)-induced acute lung injury; however, the underlying mechanism is still unclear. To investigate, an acute lung injury mouse model was induced by intraperitoneal injection of LPS. Histopathological changes were determined by hematoxylin and eosin staining. Enzyme-linked immunosorbent assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 33 publications
1
18
0
Order By: Relevance
“…ETS2 is a target of miR-381-3p, and the MAPK/miR-381 axis is involved in epithelial-mesenchymal transition in lung cancer 11 . More importantly, miR-381 is involved in the treatment of lipopolysaccharide (LPS)-induced acute lung injury by dexmedetomidine 12 . The same study also predicted that miR-381-3p was regulated by long non-coding RNA (lncRNA) Kcnq1 opposite strand/antisense transcript 1 (Kcnq1ot1) through competitive binding.…”
Section: Introductionmentioning
confidence: 99%
“…ETS2 is a target of miR-381-3p, and the MAPK/miR-381 axis is involved in epithelial-mesenchymal transition in lung cancer 11 . More importantly, miR-381 is involved in the treatment of lipopolysaccharide (LPS)-induced acute lung injury by dexmedetomidine 12 . The same study also predicted that miR-381-3p was regulated by long non-coding RNA (lncRNA) Kcnq1 opposite strand/antisense transcript 1 (Kcnq1ot1) through competitive binding.…”
Section: Introductionmentioning
confidence: 99%
“…mir-381 has been reported to be dysregulated in various cancers (20)(21)(22), but few studies have focused on the role of mir-381 in cHd. a recent study demonstrated that overexpression of mir-381 in raW264.7 cell lines decreased the concentrations of il-1β and TnF-α (42). in addition, mir-381 can reduce inflammation and the infiltration of macrophages by targeting high-mobility group box 1 mrna (43).…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, Dex attenuated pancreatic inflammatory response in mice with pancreatitis by reduction in NLRP3 activation [16]. In lipopolysaccharide-induced acute lung injury, Dex inhibited NLRP3 activation through the up-regulation of miR-381 and miR-381-mediated degeneration of NLRP3 [17]. Lv et al [18] reported that Dex promotes liver regeneration in mice after 70% partial hepatectomy by suppressing NLRP3 inflammasome and not TLR4/NF-κB, since NLRP3 inhibition is associated with better liver regeneration and liver function recovery, while NF-κB inhibition conversely diminished liver regeneration.…”
Section: Discussionmentioning
confidence: 99%